Fruit extract derived from a mixture of noni, pineapple and mango capable of coagulating milk and producing curd with antidiabetic activities - Palliah, Jaya Vejayan; Bathmanathan, Rupbansraaj; Tuan Said, Sharifah Aminah; Chakravarthi, Srikumar; Ibrahim, Halijah (PubMed, 2022)
Summary: Research background. Morinda citrifolia L. (noni), Ananas comosus L. cv. Sarawak (pineapple) and Mangifera indica L. cv. Apple (mango) represent fruits capable of coagulating milk and forming a curd. Plant-derived milk coagulants have antidiabetic phytochemicals that enrich the curd. Hence this work evaluates the dual benefits of the fruits in coagulating milk and the antidiabetic activities found in the obtained curd. Experimental approach. The three fruits were mixed to form a supercoagulant (a milk coagulant mixture of the extracts at a ratio of 1:1:1), and the milk coagulation time was measured. The milk was coagulated by the supercoagulant, and thus fortified curd was tested for its ability to inhibit α-glucosidase and α-amylase activities. Then, the fortified curd was fed daily to streptozotocin-induced diabetic rats and their biochemical markers such as blood glucose level, aspartate aminotransferase, alanine transaminase, etc. as well as histopathology of their liver and kidney tissues were compared with the untreated diabetic rats and normal rats. Results and conclusions. The supercoagulant had a milk coagulation time of (28±3) s at a 50 mg/mL concentration. Its fortified curd inhibited α-glucosidase and α-amylase activities, with IC50 values of (4.04±0.03) and (3.42±0.02) mg/mL, respectively. The average mass of the streptozotocin-induced diabetic rats fed daily with curd formed by the supercoagulant was (201±10) g on day 20 compared to diabetic control rats with (149±16) g. The blood glucose concentration for rats treated with the supercoagulant after fasting was (15±1) mmol/L compared to the diabetic control rats ((26±2) mmol/L). Blood tests on the treated rats showed aspartate aminotransferase, alanine transaminase, γ-glutamyl transferase and alkaline phosphatase (liver function tests) amounts of (214±78), (91±13), 3 and (510±38) U/L, respectively, while the total protein and renal function tests showed the concentrations of albumin, globulin, urea and creatinine of (37±2) g/L, (30±2) g/L, (11±1) mmol/L and (42±3) μmol/L, respectively. These concentrations were found to be similar to those of the normal rats on day 20. Furthermore, a histopathological study performed on the liver and kidney of the rats found no apparent damage. Novelty and scientific contribution. This supercoagulant derived from a mixture of fruits is able to coagulate milk rapidly, and its curd is fortified with safe antidiabetic agents. The supercoagulant is potentially useful in producing functional dairy food to prevent diabetes or as a supplement for diabetics to control their blood sugar. Such products are capable of replacing dairy products derived from animal enzymes and provide consumers with additional functional dairy products..